Anteseden dari kinerja usaha skala kecil dan menengah: Peran orientasi kewirausahaan dan dukungan pemerintah - Anisa Fauziah Danil; Perengki Susanto (Universitas Negeri Padang, 2021)
The focus of this study is to look at performance of SMEs in Padang Pariaman Regency, particularly the role of entrepreneurial orientation and government support as antecedents. The method used in this study was a quantitative. The owners-managers of SMEs in Padang Pariaman Regency made up the study's population. The sample size for this study was 140 respondents, and the sampling technique was non-probability. SEM analysis with Smart-PLS (PLS-SEM) was used as an analysis approach. The findings of this study show that: (1) innovation has no impact on performance; (2) proactive has no effect on performance; (3) risk-taking has a significant impact on performance; (4) aggressiveness has an impact on performance; (5) autonomy has a significant impact on performance; and (6) government support has a significant impact on performance. The implications will be provided in the chapter.Keywords: Innovation, pro-active, risk taking, aggressive, autonomi, government support, SMES performance